HOW TO CROWDFUND AND FINTECH ARE DYNAMIC - Kannika Kanok; Chai Niran (International Journal of Law and Legal Ethics, 2021)
In the Industry 4.0 model, innovation and technology are used to innovate business models, with special attention to repeatable and scalable business models. This study uses Thailand as a case study to study the opportunities and challenges of fintech startups. Using the second-hand data obtained from the Thai Fintech Association and the main data collected from in-depth interviews, a hybrid method was adopted. Descriptive analysis and content analysis are used to obtain robust results. The empirical results show the profile of Thai fintech companies and how they bring opportunities and challenges to development and growth. The survey results show that these opportunities and challenges are the result of the national technology system and financial supervision, the symbiotic relationship, and the interrelationships generated through digital literacy, financial literacy, and financial inclusion. The study discusses each factor in detail and proposes suggestions for further studies. The findings could be used by policy makers and local authorities to make improvements, as well as minimize the potential risks for FinTech startup firms and contribute to sustainability in the economy as a whole.